Effects of slightly acidic electrolyzed water ice and grapefruit seed extract ice on shelf life of brown sole (Pleuronectes herzensteini) - Jung, Sun; Ko, Bong Soo; Jang, Hye-Jin; Park, Hee Jung; Oh, Se-Wook (Food science and biotechnology, 2018)
The effects of slightly acidic electrolyzed water ice (SAEW-ice) and grapefruit seed extract ice (GSE-ice) on changes in brown sole quality during storage were determined using microbial, chemical, and sensory analyses to prolong the shelf life of brown sole. Microbiological analyses showed that GSE-ice storage was more effective for inhibiting the growth of total plate count, Pseudomonas , and H 2 S-producing bacteria than SAEW-ice storage. Chemical indexes of brown sole showed that SAEW-ice and GSE-ice storage extended the shelf life of fish compared with TW-ice. Sensory scores following GSE-ice storage were higher than those following storage under the other conditions. Taken together, the present study indicated that the quality of brown sole was maintained for 9–10 days in TW-ice, and 11–12 days in SAEW-ice and 12–13 days in GSE-ice. Therefore, ice storage using SAEW-ice and GSE-ice effectively extended the shelf life of brown sole.